FLOOD POTENTIAL IN THE DOWNSTREAM OF CITARUM RIVER, MUARA GEMBONG, BEKASI DISTRICT, WEST JAVA - Patonah, Aton; Tresnasari, Endah; haryanto, edi tri; rendra, pradnya p. raditya; sabily, zulfa; sukiyah, emi; sulastri, murni; abdurrohman, Muhammad jihad; putera, alvindo andreansyah; Subagja, Agam; ridwan, panji (Journal of Geological Sciences and Applied Geology, 2019)
The flood can affect an area so cause great loss. Muaragembong is one of the sub-districts in Bekasi Regency. This area is known as an area that is regularly hit by floods. The purpose of this study is to analyze changes in flood areas, specifically those related to residential areas. The results showed significant changes in the flood area from 1993 to 2016. Increased changes in land use from swampy areas and mangrove forests to residential areas are thought to be the cause of the increase in flooding every year. One way to reduce the impact of flooding in Muaragembong is to restore the existence of mangrove forests along the Citarum River to the sea.Keywords: Flood, Muara Gembong, Citarum River, Land Use